Studies on Homalomeneae (Araceae) of Borneo VI: Homalomena giamensis, a New Species from Sarawak, Malaysian Borneo, with Observations on its Pollination - Soon, T Lay; Wong, Sin Yeng; Boyce, P.C (International Aroid Society , Inc., 2010)
A new species, Homalomena giamensis L.S.Tung, S.Y.Wong & P.C.Boyce, is described and illustrated from karst limestone formations at Kampung Giam, Kuching Division, SW Sarawak, to where it is locally endemic. As part of an ongoing project to investigate triggers and barriers in speciation processes in Homalomena, observations of the pollination of Homalomena giamensis were undertaken to record inflorescence mechanics, interactions with insect visitors, and determine the pollinator. Five insect genera visited during anthesis-Diptera: Drosophilidae (Colocasiomyia); Coeleoptera: Chrysomelidae: (Chaloenus & Dercetina sp.); Nitidulidae (genus undetermined), and Scarabaeidae: Rutelinae (Parastasia bimaculata Guerin). The pollinator was determined to be the ruteline scarab. Parastasia bimaculata is a rather widespread species in tropical Asia, and has previously recorded as a pollinating agent for one Bornean Homalomena. A review of pollination studies of tropical Asian aroids to date is given.